THE ANALYSIS OF FACTORS INFLUENCING VEHICLE SUPPLY IN THE HEALTH SECTOR: A CASE OF MINISTRY OF HEALTH TANZANIA - Shauritanga, Joseph; Nyaki, Prosper (AGUSPATI Research Institute, 2025)
The study analyzed the factors influencing vehicle supply in the Health Sector in Tanzania, a case of Ministry of Health in Tanzania. A total of 96 respondents participated in the study, representing a full response rate. Data were collected using structured questionnaires and analyzed through reliability tests, descriptive statistics, regression analysis, correlation, and ANOVA. The findings revealed that health service delivery needs, policy on vehicle supply, and budget allocation are key determinants of vehicle supply. Health service delivery needs were found to be important in shaping demand for vehicles, particularly through the number of Health Sector facilities served and the frequency of travel required. Policy factors, including procurement requirements and compliance with safety and environmental standards, were also shown to influence vehicle supply. Budget allocation emerged as another critical factor, especially the ability to adjust budgets and provide adequate funding for vehicle procurement. The study concludes that vehicle supply in the Ministry of Health is shaped by the interplay of operational requirements, institutional policies, and financial planning. It emphasizes that ensuring adequate and timely vehicle supply requires a holistic approach that integrates these three elements. The study recommends that the Ministry and government improve budget responsiveness, update procurement policies, and ensure compliance with standards, while stakeholders and communities should support resource mobilization to strengthen the supply system.